Surgical Practice in the Current COVID-19 Pandemic: A Rapid Systematic Review - Flávio Carneiro Hojaij; Lucas Albuquerque Chinelatto; Gustavo Henrique Pereira Boog; Júlia Adriana Kasmirski; João Vitor Ziroldo Lopes; Fernando Mauad Sacramento (Clinics)
The coronavirus disease (COVID-19) outbreak </mac_aq>started in Wuhan, China, in December 2019, and evolved into a global problem in a short period. The pandemic has led to many social and health-care challenges. In this context, surgery is an area that is facing the need for many adaptations. In this systematic literature review, we analyzed different perspectives concerning this situation, aiming to provide recommendations that could guide surgeons and </mac_aq>entities toward screening, elective and emergency surgeries, decision making, and operating room management. A computerized search in PubMed, Scopus, and Scientific Electronic Library Online (SciELO) for relevant literature up to April 4, 2020, was performed. Articles were included if they were related to surgery dynamics in the context of the COVID-19 pandemic. Of the 281 articles found in our initial search and 15 articles from alternative sources, 39 were included in our review after a systematic evaluation. Concerning preoperative testing </mac_aq>for severe acute respiratory syndrome coronavirus 2 infection, 29 (74.4%) articles recommended some kind of </mac_aq>screening. Another major suggestion was postponing all (or at least selected) elective operations (29 articles, </mac_aq>74.4%). Several additional recommendations with respect to surgical practice or surgical staff were also assessed and discussed, such as performing laparoscopic surgeries and avoiding the use of electrocauterization. On the basis of the current literature, we concluded that any surgery that can be delayed should be postponed. COVID-19 screening is strongly recommended for all surgical cases. Moreover, surgical staff should be reduced to the essential members and provided with institutional psychological support.